Ultrathin Si/CNTs Paper-Like Composite for Flexible Li-Ion Battery Anode With High Volumetric Capacity - Fu, Jinzhou; Liu, Hao; Liao, Libing; Fan, Peng; Wang, Zhen; Wu, Yuanyuan; Zhang, Ziwei; Hai, Yun; Lv, Guocheng; Mei, Lefu; Hao, Huiying; Xing, Jie; et al. (Frontiers in Chemistry, 2018)
Thin and lightweight flexible lithium-ion batteries (LIBs) with high volumetric capacities are crucial for the development of flexible electronic devices. In the present work, we reported a paper-like ultrathin and flexible Si/carbon nanotubes (CNTs) composite anode for LIBs, which was realized by conformal electrodeposition of thin layer of silicon on CNTs at ambient temperature. This method was quite simple and easy to scale up with low cost as compared to other deposition techniques, such as sputtering or CVD. The flexible Si/CNTs composite exhibited high volumetric capacities in terms of the total volume of active material and current collector, surpassing the most previously reported Si-based flexible electrodes at various rates. In addition, the poor initial coulombic efficiency of the Si/CNTs composites can be effectively improved by prelithiation treatment and a commercial red LED can be easily lighted by a full pouch cell using Si/CNTs composite as flexible anode under flat or bent states. Therefore, the ultrathin and flexible Si/CNTs composite was highly attractive as anode material for flexible LIBs.